Abundance and diversity of aquatic insects in two water bodies of Chittagong university campus (Bangladesh Journal of Zoology, 2015)
Abundance and diversity of aquatic insects was studied in two water bodies, (a pond and a lake) of Chittagong University campus during October 2009 to September 2010. A total of 4406 insects belonging to 32 genera, under 20 families and 6 orders were recorded. In both the water bodies, the representatives of the orders Hemiptera and Odonata were the most abundant groups. During the study period highest abundance of the total insects was recorded in November 2009 and the lowest in July 2010. Abundance of insects was comparatively higher in the pond habitat than in the lake. The Quotient of Similarity (QS) of the insects between the two water bodies was found to be the highest in October 2009 and lowest in July 2010. Species diversity, species richness and species evenness values of the lake were higher than that of the pond. Hydrophilus sp. and Sphaerodema sp. were the most dominant insects in the pond, while Chironomous sp. and Gerris sp. in the lake.Bangladesh J. Zool. 42(1): 19-33, 2014